Analisis Saluran dan Marjin Pemasaran Biji Kopi (Green Bean) Robusta di Desa Cugung Lalang Kecamatan Ujan Mas Kabupaten Kepahiang - Fitria, Indah; Febrianto, Sudi (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Coffee is one of the plantation commodities that has quite high economic value among other plantation crops and plays an important role as a source of foreign exchange for the country. The success of coffee agribusiness requires the support of all parties involved in the coffee production process, processing and marketing of coffee commodities. In Kepahiang Regency, coffee is a plantation commodity that is very popular with the community. This can be seen from the increase in coffee consumption in Kepahiang Regency which has experienced a significant increase. One of the weaknesses of coffee is in terms of distribution and marketing. A marketing system is said to be efficient if it can provide maximum satisfaction for producers, consumers and marketers with the lowest possible use of economic resources. The processing of coffee into Green Bean coffee carried out by farmers is to increase and maximize the income and standard of living of the farmer's household, which in the end can meet the needs of their family. To increase farmers' income, various marketing channels are used to distribute the results of coffee processing into green coffee beans from producer to consumer level. For this reason, it is necessary to carry out a more in-depth study on "Channel Analysis and Marketing Margins for Coffee Beans (green beans) in Cugung Lalang Village, Ujan District, Regency Kepahiang.